Differential response pathways of Picea asperata seedlings from different provenances to altitudinal transfer - Xie, Jiangkai; Deng, Jiayi; Liu, Tairui; Guo, Jinping; Zhang, Yunxiang; Yang, Meng (Frontiers in Plant Science, 2025)
In mountain ecosystems, the native altitude acclimation and transplantation altitude response strategies of plant seedlings may provide theoretical guidance and strong evidence for addressing the continuous reduction of species' suitable habitats caused by global changes. However, our understanding of the adaptation to native altitude, altitude gradient responses, and underlying mechanisms of native mountain tree species in North China is still unclear. We designed a field experiment in mountainous areas where seedlings from different provenance altitudes (low altitude: 1600 m; high altitude: 2400 m) were transplanted to four typical altitudes. By measuring 18 functional trait indicators related to physiology, leaf characteristics, and nutrients, we attempted to reveal the adaptation of Picea asperata to native altitude and the differential responses and mechanisms to altitude changes. The results showed that: (1) Native altitude regulated the seedling's photosynthetic strategy (Pn), water strategy (WUE, gsw), morphological strategy (SLA), and nutrient storage (N), but did not affect leaf structure (AvgPA, AvgSL, AvgSW) or carbon storage; (2) Seedlings adapted to altitude changes by altering nutrient storage (NSC, Sugar, Protein) and leaf morphology (AvgPA, AvgSL, AvgSW, SLA); (3) Low-altitude seedlings of Picea asperata exhibited environmental dynamic plasticity and achieved coordinated growth of physiological functions, leaf morphology, and carbon storage at 1900 m (the optimal altitude); (4) High-altitude seedlings showed advantages in their native environment, but their adaptability decreased with decreasing transplantation altitude, reflecting the adaptation to native environment conditions; (5) Random forest model and PLS-PM confirmed that low-altitude seedlings tended to adjust leaf morphology to regulate leaf nutrients and photosynthetic physiological functions, while high-altitude seedlings regulated physiological functions by adjusting leaf nutrient changes. Seedlings from different provenance altitudes had differential adaptation pathways and regulatory strategies in response to altitude changes.